Chopin and the Warsaw literati - part two - Nowicka, Elżbieta (Interdisciplinary Studies in Musicology, 2018)
Chopin’s life in Warsaw fell at a time of important phenomena and processes in history, the arts, aesthetics, etc. This article deals with the artistic and social milieu to which the composer belonged and looks at the question of the common artistic imagination and aesthetic ideas elaborated within that environment, based on the example of Chopin and two poets: Stefan Witwicki and Dominik Magnuszewski. Chopin’s relationship with Witwicki, which gave rise to his songs to the poet’s texts and lasted into their time in exile, is considered in respect to discussion on folk culture that was on-going at that time. That culture was treated as a sign of the nobly archaic or else as a manifestation o f modern art, of the “art of the future”. These convictions did not function as alternatives; their overlapping characterised various aspects of early romanticism. The output of Magnuszewski, meanwhile, shows the transformation of traditional figures of rhetoric into Romantic means of expression. It displays a style of writing that constitutes an act o f Romantic hermeneutics in respect to the language of tradition. Avoiding simple comparisons of works of very different artistic level and significance, the author analyses Chopin’s relationships with the two poets by reference to the generational experience - as variously understood - of creative artists born during the first decade of the nineteenth century, which connected artists of different levels of talent and varying individual fortunes.